PREFERENSI KONSUMEN IKAN LAUT SEGAR BENGKULU ATAS BRAND EQUITY SEBAGAI JAMINAN KUALITAS PRODUK - Bonodikun, Bonodikun; Asriani, Putri Suci; Budiyanto, Budiyanto (Jurnal AGRISEP, 2014)
Fisheries products in Bengkulu Province are still not to be classified well, so it may be considered not necessary to develop the discourse of product quality assurance. Regardless, the demands of globalization require each manufacturer to think ahead about the quality of the product "deserves" to be marketed, both in terms of the beneficial, characteristic, and image. Consumers have ample opportunity to get a product that is "inappropriate" according to his preference, one of which is through the use of brand equity as a guarantee of product quality as measured by the consumer response to price and product. The purposes of this study are: (1) to explain the relationship between the beneficial variables, characteristic, and the image of the brand equity variables, and (2) to analyze consumer response to the presence of the brand. From the results of this study also noted that the level of consumer preferences towards brand used by trader fresh fish is high in the city of Bengkulu. Assessment is based on expediency consumer brand presence (beneficial), the specific features that exist on the brand/merchant customer fresh sea fish (characteristic), and the picture attached to the brand (image). Based on the results of the Pearson test is known that the beneficial variables and the use of brand image on fresh fish merchant in the city of Bengkulu has a positive relationship to brand equity inherent in the product. Furthermore, it’s also obtained information that the consumer response to the presence of a brand that is used by trader fresh fish in the city of Bengkulu as a guarantee of quality is very good.